Follicular T cells are clonally and transcriptionally distinct in B cell-driven mouse autoimmune disease - Elliot H. Akama-Garren (Nature Portfolio, 2021)
Follicular T cells regulate germinal centre reactions, but their phenotypes in autoimmune disease are unclear. Using a mouse model of autoantibody disease, the authors show that autoimmune follicular T cells differ by TCR clonotype and transcriptional profile from non-autoimmune follicular T cells.